Gender representation among speakers at the Japanese Society of Anesthesiologists meetings: A retrospective analysis - Michiko Kinoshita; Yoko Sakai; Katsuya Tanaka (PLoS ONE, 2025)
Purpose This study investigates the gender distribution of speakers at the Japanese Society of Anesthesiologists (JSA) annual and branch meetings of the Japanese Society of Anesthesiologists. Methods We examined the gender of speakers in sessions at both JSA annual and branch meetings. We also verified the speakers’ Japanese medical licensure status and years of qualification. Results We analyzed 383 sessions from JSA annual meetings between 2019 and 2024, which included 827 speaker slots. Of them, 679 (82.1%) were men and 148 (17.9%) were women. Women were significantly underrepresented in sessions with fewer speaker slots (chi-square test, p =  0.006; trend test, p <  0.001). Furthermore, sessions were frequently composed entirely of men: 73.1% of all sessions and 44.3% of panel presentations were solely male participants. Among the subspecialties, female representation was high in obstetric anesthesia (36.8%) and pediatric anesthesia (31.8%) but low in cardiovascular anesthesia (6.3%). Among 508 speakers with confirmed Japanese medical licenses, 425 (83.7%) were men, and 83 (16.3%) were women, with no significant differences in gender distribution based on the year of licensure (Fisher’s exact test, p =  0.968; trend test, p =  0.463). Additionally, we examined 104 sessions from JSA branch meetings between 2019 and 2023, comprising 176 speaker slots. Of them, 147 (83.5%) were men and 29 (16.5%) were women. There was no significant difference in gender distribution among branch meetings across different regions (p =  0.984). Conclusion These findings underscore the need for proactive measures to promote gender diversity in Japan’s anesthesiology field.